Description of Discipline Exercise of Student Driving Training in LKP Nusantara, Padang - Pebriadi Chan; Setiawati Setiawati (Universitas Negeri Padang, 2019)
The research was distributed it is alleged by a reliable and professional instructors instill discipline is very well seen 60 people citizens learn to adhere to all applicable rules, his presence is high, his zeal to present and is active in the following training activities are driving. Type of this research is quantitative descriptive. The population in this 60 people. Samples taken by as much as 50%. The number of s ampel is as many as 30 people. This research data analysis techniques using a percentage. The research results showed that the construction of the discipline in this aspect of the regulations categorized very well given by the instructor, the construction of the discipline in the aspect of punishment is categorized very well given by the instructor, in the aspect of discipline construction the award is categorized very well provided by the instructor. This is evidenced most warag study stated